Dangerous skills gap leaves organisations vulnerable. Issue 8 (August 2016) - Rafferty, Ben
Abstract : These days, not only are businesses having to contend with increasingly sophisticated attacks on data, they are also facing a serious skills gap within the professions that should be responsible for preventing these attacks. In the security landscape, this role can have a number of job titles – security engineer, security analyst, ethical hacker, penetration tester, security researcher. But they all have one goal – to identify and report on vulnerabilities within security systems. Not only are businesses having to contend with increasingly sophisticated attacks on data, they are also facing a serious skills gap within the professions that should be responsible for preventing these attacks. As the threat of data breaches continues to grow for business across the globe, the role of penetration testers and ethical hackers is only going to become more important. And while the need for penetration testing may once have resided purely in the domain of government departments, large organisations, multinational corporations and financial institutions, it is now viewed as an essential data security strategy for companies of all shapes and sizes, says Ben Rafferty of Semafone.